Inhibition of arachidonic acid metabolism by the Andean crude drug Parastrephia lucida (Meyen) Cabrera - D'almeida, Romina Elisa (2013)
Ethnopharmacological relevance: Parastrephia lucida (Meyen) Cabrera is used in the traditional medicine of Argentinean highlands as an antiseptic and anti-inflammatory medicinal plant. To give scientific support to the ethnopharmacological claim of Parastrephia lucida as an anti-inflammatory crude drug the effect of Parastrephia lucida extracts and fractions was assessed on key enzymes of the biosynthesis of pro-inflammatory eicosanoids mediators from arachidonic acid (AA). Materials and methods: A bio-guided fractionation of the plant extract was carried out to find out the compounds or mixtures responsible for the anti-inflammatory effect. The extracts and fractions were tested in vitro for their ability to inhibit the enzymes cyclooxygenase (COX)-1 and COX-2, lipoxygenase (LOX) and phospholipase (sPLA2). Fractions were analyzed by HPLC-MS, HPLC-ESI-MS/MS and NMR to relate the effect with groups of secondary metabolites. Results: Parastrephia lucida was more effective inhibiting COX and sPLA2 than LOX. Assay-guided isolation led to the active fractions C and F which showed different effect on the selected enzymes. The fraction C was more effective inhibiting LOX while fraction F showed better activity against sPLA2 and COX-2. Both fractions were further worked-up following the isolation of the anti-inflammatory agents with the selected enzyme assays. The main compounds identified in the most active fractions were 5,4′-dihydroxi-7-methoxyflavanone, apigenin, apigenin methyl ether and apigenin trimethyl ether, methyl and dimethyl ethers from quercetin, kaempferol and luteolin methyl ether, ferulic acid esters, cinnamic acid and vanillin. Conclusions: Parastrephia lucida extract inhibit AA metabolism via several enzymes. The results give support to the traditional use of this plant for the treatment of inflammatory disorders.